PENINGKATAN KEMAMPUAN MEMBACA PERMULAAN MELALUI METODE FUN LEARNING DENGAN MENGGUNAKAN MEDIA KARTU HURUF DI KELAS 1 SD MUHAMMADIYAH KOTA UTARA - Rahmadani Muhidin; Lamsike Pateda; Sitti Rahmawati Talango (Al-mujahidah, 2025)
This study aims to determine the use of the Fun Learning method with the use of letter card media can improve early reading skills in grade 1 of Muhammadiyah Elementary School, North City. The problem that often occurs in the learning process in grade 1 of Muhammadiyah Elementary School, North City is that 78.3% or around 15 out of 20 students are still unable to recognize the letters F, G, K, L, Q, R, V, W, X, making it difficult for students to read the beginning. Fun Learning method and the use of Letter Card Media. The results of student observations in cycle 1, students who achieved learning success in cycle 1 were 11 people, the results of teacher observations with a percentage of 70% (Not Successful). The results of student observations in cycle 2, students who achieved learning success were 17 people with a percentage of 85%. The results of teacher observations with a percentage of 88.3% (Successful). It can be concluded that the increase in early reading skills from the percentage of cycle 1 by 55% to cycle 2 by 85% and experienced an increase of 30% which is very good for the success of a study.